A comparative study of density of obturated root canals by conventional and mechanical lateral condensation techniques - Hasan Abedi; Shahriar Shahriari; Seyed Mohsen Jalalzadeh; Reza Moradkhany (Wolters Kluwer Medknow Publications, 2009)
Background: The purpose of this study was to compare the weight of root canal filling material used in a new lateral condensation technique named mechanical lateral condensation (MLC) with that of conventional lateral condensation technique (LC). This new technique uses reciprocal handpiece. Methods: In this experimental study, 40 human extracted straight canine teeth were used. After crown amputation, root canals were prepared with 18 mm in length. The teeth were randomly divided into four experimental groups; each group was consisting of 10 teeth. The teeth in groups IA and IB were filled by LC technique. The teeth in groups IIA and IIB were filled by MLC technique and using a finger spreader that placed in a reciprocating-action handpiece to laterally condense cold gutta-percha, creating space for accessory cones. All of the roots were weighted before and after obturation and the difference demonstrated the weight of gutta-percha mass. The data were analyzed by t-test. Results: The mean weight for MLC obturations was 10.82 ± 0.025 g compared with 7.37 ± 0.035 g for that of LC technique. The difference was statistically significant (P = 0.001). Conclusion: This study showed that MLC technique requires more gutta-percha mass than LC technique.